1997
DOI: 10.1038/sj.sc.3100351
|View full text |Cite|
|
Sign up to set email alerts
|

Survival and cause of death after traumatic spinal cord injury. A long-term epidemiological survey from Denmark

Abstract: Life expectancy among individuals with spinal cord injuries (SCI) has remained lower than in the normal population, even with optimal medical management. But signi®cant improvement has been achieved, as will be illustrated in this retrospective study of an unselected group of traumatic survivors of SCI, dead or still living. There has been a complete follow-up over 4 decades, information being obtained from available medical records, death certi®cates, and post mortem records. The survey included a total of 88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
85
4
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(104 citation statements)
references
References 12 publications
9
85
4
6
Order By: Relevance
“…1,3 In this report, the analysis of cardiac structure and function in a sample of young, nonhypertensive, nondiabetic nonsmoker individuals revealed that (1) subjects with SCI exhibited an impaired LV diastolic function in comparison with the able-bodied ones; (2) diastolic dissimilarities between SCI and healthy subjects persisted after adjusting for hemodynamic and inflammatory parameters; (3) worse LV diastolic function was paralleled by a pattern of LV concentric remodeling among subjects with SCI. Overall, these data suggest that subjects with SCI exhibit alterations in LV diastolic function independently of traditional cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…1,3 In this report, the analysis of cardiac structure and function in a sample of young, nonhypertensive, nondiabetic nonsmoker individuals revealed that (1) subjects with SCI exhibited an impaired LV diastolic function in comparison with the able-bodied ones; (2) diastolic dissimilarities between SCI and healthy subjects persisted after adjusting for hemodynamic and inflammatory parameters; (3) worse LV diastolic function was paralleled by a pattern of LV concentric remodeling among subjects with SCI. Overall, these data suggest that subjects with SCI exhibit alterations in LV diastolic function independently of traditional cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 73%
“…1,2 Previous studies demonstrated that subjects with SCI exhibit higher atherosclerotic burden in comparison with able-bodied individuals. 3 Interestingly, this process is not explained by traditional cardiovascular risk factors, indicating that alternative mechanisms might influence the development of early atherosclerosis in such individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The value of such prompt therapeutical reaction has been illustrated clearly over the years by the marked decrease in renal deaths after spinal cord injury during the last half century. 11,12 Urodynamic investigation will objectivate the pathological parameters and will permit a guide to the choice of treatment. In the patient presented here anticholinergic drugs were prescribed and bladder emptying was changed from straining to selfcatheterization.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of death after spinal cord injury (SCI) have changed from being primarily due to urinary tract diseases increasingly to being caused by cardiovascular diseases and respiratory complications, [1][2][3][4] thus becoming more similar to the causes of death in the general population. This is at least true in centres providing centralized care for individuals with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…6 The longevity in persons with SCI still remains below the life expectancies in the general population. [1][2][3]7,8 Because of the increasing prevalence of individuals living with SCI, both traumatic and nontraumatic lesions, there is an increasing need for data pertaining to SCI. To facilitate comparisons regarding injuries/lesions, treatments and outcomes between patients, centres and countries, such data should be in the form of common international data sets collected on individuals with SCI.…”
Section: Introductionmentioning
confidence: 99%